PENGARUH PENGELOLAAN MASALAH PELANGGAN, EDUKASI PELANGGAN DAN PARTISIPASI PELANGGAN TERHADAP LOYALITAS PELANGGAN - Jatmiko, Robby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This research analyses the influence of customer participation,customer problem management, and educational customer to customerloyalty. Technique of sampling applied is accidental sampling method.The responders in this research are 121 responders, and all responderare customers of Vitalac. Tool of data analysis’s used is usingcomputer program of SPSS.The result of data analysis shows that the model developed and theresearch result can be accepted. Hereinafter, the result proves thatthere is positive influence of customer participation, customer problemmanagement, and educational customer to customer loyalty.